Implementation Of Performance Management In J&T Cargo Tanjungpinang - Ade Septiany; Satriadi Satriadi; Inthira Cahyadiani; Putri Delya; Tri Mardini (Pusat Riset dan Inovasi Nasional, 2024)
At the J&T Cargo Tanjungpinang company, performance management is very much needed because performance management has an important role. The aim of this research was to find out how the Deming model performance management system is implemented for employees by JNT Cargo Tanjungpinang. The method used in this research is a descriptive method with a qualitative approach and uses data collection methods through interviews, observation and documentation. The results of this research show that J&T Cargo Tanjungpinang has implemented the Deming model of performance management by carrying out good PDCA stages. However, there is still a need to increase and improve productivity in order to overcome the problems that occur by carrying out evaluations and development as well as capabilities to create quality human resources.